THE INFLUENCE OF DIGITAL LITERACY ON CONSUMER PERCEPTIONS AND E-COMMERCE ENGAGEMENT - Muhammad Saad Ullah; Muhammad Kabir Khan; Gardashov Rashad Ahmadxan Oglu; Tahira Yasmin (Policy Research Journal, 2025)
This study investigates the influence of digital literacy, perceived usefulness, and perceived ease of use on online purchase intention among Internet users in Pakistan. An extended version of the Technology Acceptance Model (TAM) was applied, incorporating digital literacy as a key factor. A quantitative approach was used, with 298 participants completing a survey. The data were analyzed using Partial Least Squares Structural Equation Modeling (SEM-PLS) to test the proposed framework. The results show that digital literacy significantly impacts perceived usefulness, perceived ease of use, and online purchase intention. Higher levels of digital literacy lead to stronger perceptions of the perceived usefulness and ease of use and online shopping, which, in turn, enhance users' intention to purchase online. Both perceived usefulness and perceived ease of use were found to significantly affect online purchase intention, highlighting their roles in shaping users’ online shopping behavior. This research emphasizes the importance of digital literacy in influencing online shopping. The findings suggest that improving digital literacy among Internet users can enhance their perception of online shopping platforms, encouraging more frequent online purchases. This has important implications for businesses and policymakers aiming to increase e-commerce adoption in Pakistan.